Machine learning-supported detection, FTIR characterization and estimated dietary intake of microplastics in bottled water and beverages in western Mexico - Cristian M. Hernández-Covarrubias; Roberto Muñiz-Valencia; Griselda Membrila-González; Silvia G. Ceballos-Magaña; Vilma del C. Salvatierra-Stamp; Eulogio Orozco-Guareño; Alejandro A. Peregrina-Lucano (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Assessing pesticide pollution in surface water of two basins in western Mexico: spatiotemporal variability, potential ecological risk assessment, and pesticides prioritization - Andrea Rodríguez García; Brian A. Rodríguez-Aguilar; Silvia G. Ceballos-Magaña; Alejandro A. Peregrina-Lucano; Raul Calderón-Araya; Paulina Palma-Rubilar; Roberto Muñiz-Valencia; Emmanuel O. Helguera-Gómez (Environmental Monitoring and Assessment, 2026)

From blueprint to biocontrol: Integrating complete genome, metabolic profiling and in vivo evaluation of Xenorhabdus magdalenensis IMI397775 for insect pest control - Catalina A. Painenao; Jasmín G. Taladriz; Muriel N. Neculpán; María José Vargas-Straube; Jamie Bojko; Ricardo Ceballos; Natalí Fernandez; Patricia D. Navarro (Journal of Invertebrate Pathology, 2026)

First records of multiple paternity in the softnose skates, family Arhynchobatidae: Sympterygia acuta as a case study - Victoria M. Lenain; Cynthia A. Awruch; Santiago G. Ceballos; Christine Dudgeon; Valeria Gabbanelli; Florencia Matusevich; Ezequiel Mabragaña (Hydrobiologia, 2026)

Regional aerosol transport and vertical mixing: factors contributing to an air pollution event in a highly urbanized Andean valley - G. Alexis Ayala-Parra; K. Santiago Hernández; Camilo A. Chalán; Mauricio Ramírez; Manuel D. Zuluaga; Lina I. Ceballos; J. Alejandro Martínez (Atmospheric Research, 2026)

Anti-hyperglycaemic effect of aqueous extract from Brosimum alicastrum: in vivo evaluation and quantification of its components by HPLC-DAD - Lina Barragán-Mendoza; Rolando Garnica-López; Mario Alberto Gaitán-Hinojosa; Lisa Dalla Via; Silvia G. Ceballos-Magaña; Hortensia Parra-Delgado (Natural Product Research, 2025)

Regulation of HvASN1 expression by bZIP transcription factors during barley embryo development and germination - Estefanía Contreras; Rosario Alonso; Elena Pastor-Mora; Mar G. Ceballos; Jesús Vicente-Carbajosa; Raquel Iglesias-Fernández (Planta, 2025)
Main conclusion Our findings provide new insights into the molecular mechanisms that regulate N metabolism in barley and potentially other cereal crops, offering valuable perspectives for enhancing N use efficiency in agricultural practices. Abstract Efficient nitrogen (N) utilization is essential for plant growth, especially during seed development and germination. In barley ( Hordeum vulgare ), the asparagine synthetase gene HvASN1 is essential for nitrogen transport and storage, synthesizing asparagine, a key molecule in N recycling. The phylogenetic analysis indicates that HvASN1 clusters with Arabidopsis AtASN1 and shares high similarity with HvASN2, suggesting a conserved role in N metabolism. A detailed characterization of a ~ 500 bp HvASN1 promoter region revealed a conserved GCN-like cis -element. Transient expression assays in Nicotiana benthamiana demonstrated that the wild-type promoter significantly increases luciferase activity under dark conditions, whereas mutation of the GCN-like element reduces this activity, highlighting its role in light-responsive gene regulation. Further investigation identified the bZIP transcription factor HvbZIP53 as an activator of the HvASN1 promoter through binding to the GCN-like element. This activation is finely tuned by sucrose via a conserved upstream open reading frame (uORF) in HvbZIP53’s 5′ UTR, which mediates sucrose-induced repression of translation. Additionally, yeast two-hybrid assays and transient expression studies in Arabidopsis provided evidence that HvbZIP53 physically interacts with HvBLZ1, a C group bZIP factor, resulting in a synergistic enhancement of HvASN1 expression. The spatial and temporal expression analyses further revealed that HvASN1 , HvbZIP53 , and HvBLZ1 are co-expressed in key seed tissues during development and germination. These findings indicate a complex regulatory network integrating environmental and metabolic signals to modulate N metabolism in barley, with implications for improving N use efficiency in cereal crops.

Glacial History and Ecological Restrictions Shape Island‐Scale Genetic Structure and Demography in the Southernmost Bird of Prey - Ulises Balza; Nicolás A. Lois; Katie J. Harrington; Fabiola León; Klemens Pütz; Andrea Raya‐Rey; Santiago G. Ceballos (Journal of Biogeography, 2025)
Aim To understand the influence of Andean uplifts and glacial cycles on South American biodiversity, we delve into the population genetics and evolutionary history of a unique subantarctic island raptor specialised in exploiting marine food webs. Location Islands in Tierra del Fuego and Malvinas/Falklands. Time period Last glacial period to the present. Taxon Phalcoboenus australis . Methods We used RAD sequencing to assess genetic diversity, population structure and to model demographic history through descriptive and hypothesis‐based evolutionary methods. Results We found evidence of two independent lineages: one inhabiting the Fuegian archipelago and the other one occurring in the Islas Malvinas/Falkland Islands, with the latter presenting higher genetic diversity and evidence of finer‐scale population structure. The best supported demographic scenario places the divergence time of these lineages during the last glacial period (ca. 50,000 years ago), with the occurrence of gene flow during the first 27,000 years after their divergence. Recent demographic modelling supports the general pattern of increasing genetic variability as landmasses were uncovered following the glacial period (i.e., the Fuegian archipelago) in contrast with a decrease in genetic diversity associated to island fragmentation (i.e., in the Islas Malvinas/Falkland Islands). Main Conclusions We propose that post‐glacial sea level rise and the subsequent isolation across the submerging Patagonian Shelf have driven population fragmentation and recent genetic structure in this species. Our findings advocate for recognising the two identified divergent lineages as distinct conservation units. We highlight the intricate interplay of ecological factors, glacial cycles and population dynamics in shaping the evolutionary trajectory of this unique and threatened raptor species in southern South America.

Spatiotemporal variability of pesticides concentration in honeybees (Apis mellifera) and their honey from western Mexico. Risk assessment for honey consumption - Brian A. Rodríguez-Aguilar; Alejandro A. Peregrina-Lucano; Silvia G. Ceballos-Magaña; Andrea Rodríguez-García; Raul Calderon; Paulina Palma; Roberto Muñiz-Valencia (Science of The Total Environment, 2024)

Underground speciation: Unraveling the systematics and evolution of the highly diverse tuco-tucos (genus Ctenomys) with genomic data - Ivanna H. Tomasco; Santiago G. Ceballos; Ailin Austrich; Federico Brook; Diego A. Caraballo; Gabriela P. Fernández; Cecilia Lanzone; Matías S. Mora; Andrés Parada; R. Tatiana Sánchez; Enrique P. Lessa (Molecular Phylogenetics and Evolution, 2024)

Assessing the environmental pesticides impact of river sediments from a basin in western Mexico: Spatiotemporal distribution, risk assessment of aquatic invertebrates and pesticides prioritization - Brian A. Rodríguez-Aguilar; Alejandro A. Peregrina-Lucano; Luis M. Martínez-Rivera; Silvia G. Ceballos-Magaña; Roberto Muñiz-Valencia (Science of The Total Environment, 2024)

Density and magnetization models for the Acoculco geothermal field by joint 3D inversion - M.A. Perez-Flores; Jonathan Carrillo; E. Schill; A. Lopéz-Hernández; G. Sosa-Ceballos; N. Cornejo-Triviño; A. Jiménez-Haro; M.E. Boijseauneau-López (Geothermics, 2024)

The role of species composition in montane reforested areas to offset carbon emissions - Yohana G. Jimenez; H. Ricardo Grau; Romina D. Fernandez; Sergio Javier Ceballos; Cecilia Blundo; Agustina Malizia; Julieta Carilla; Oriana Osinaga Acosta; Ezequiel Aráoz (Remote Sensing Applications: Society and Environment, 2023)

Occurrence and temporal distribution of oxandrolone and meclizine in surface water, sediments, fish muscle and otter feces of the Ayuquila-Armería basin, Mexico - Brian A. Rodríguez-Aguilar; Luis M. Martínez-Rivera; Cintia K. Rojas-Mayorga; Silvia G. Ceballos-Magaña; Ismael A. Aguayo-Villarreal; Roberto Muñiz-Valencia; Alejandro A. Peregrina-Lucano (Science of The Total Environment, 2023)

Magma plumbing system below the Popocatepetl and Iztaccihuatl volcanoes, central México, as revealed by aeromagnetic data - H. López-Loera; J. M. Espíndola; G. Sosa-Ceballos; J. L. Macías; J. Urrutia-Fucugauchi; D. E. Torres-Gaytan; F. García-Tenorio (Bulletin of Volcanology, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Improvement to quality of surface waters from rural communities: vegetable extracts as a sustainable and cheap alternative - E. Lans-Ceballos; M. Marsiglia; G. Lans-Cuesta; L. Guzman; O. Forero-Doria (Environment, Development and Sustainability, 2021)

Radiological characterization of gilthead seabream ( Sparus aurata ) by X‐ray computed tomography - Diana Ceballos‐Francisco; Nuria G. Carrillo; Francisco J. Pardo‐Fernández; Alberto Cuesta; María Á. Esteban (Journal of Fish Biology, 2020)
In recent years, the increasing use of fish as new animal models in scientific research and the growth of fish farming (mainly for human consumption) have highlighted the need for advanced technology to deepen our knowledge of fish biology. Hence, the present study was carried out to radiologically analyse the whole body of gilthead seabream ( Sparus aurata ) specimens using X‐ray computed tomography (CT). Images were acquired in an Albira SPECT/PET/CT tri‐modal preclinical‐scanner. Segmentation, measurements and three‐dimensional reconstruction were made using the Carestream Molecular imaging Albira CT system in conjunction with Pmod, AMIDE and Amira software packages. The results showed that the density values of gilthead seabream are in the range −700 to +2500 HU for the whole body. We also determined the density ranges that topographically coincide with the swim bladder, soft tissues, fat, skin and skeleton. This work describes, validates and demonstrates the application of a fully automated image analysis technique to study and quantify fish body composition, whether segmented or as a whole. In addition, the basis for applying this image technique in other in vivo studies is established.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: Harbouring the secondary endosymbiont Regiella insecticola increases predation risk and reproduction in the cereal aphid Sitobion avenae - Guillermo E. Ramírez-Cáceres; Mario G. Moya-Hernández; Manuel Quilodrán; Roberto F. Nespolo; Ricardo Ceballos; Cristian A. Villagra; Claudio C. Ramírez (Journal of Pest Science, 2020)

Single and Combined Release of Trichopria drosophilae (Hymenoptera: Diapriidae) to Control Drosophila suzukii (Diptera: Drosophilidae) - J Gonzalez-Cabrera; G Moreno-Carrillo; J A Sanchez-Gonzalez; M Y Mendoza-Ceballos; H C Arredondo-Bernal (Neotropical Entomology, 2019)

Harbouring the secondary endosymbiont Regiella insecticola increases predation risk and reproduction in the cereal aphid Sitobion avenae - Guillermo E. Ramírez-Cáceres; Mario G. Moya-Hernández; Manuel Quilodrán; Roberto F. Nespolo; Ricardo Ceballos; Cristian A. Villagra; Claudio C. Ramírez (Journal of Pest Science, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Comparative study of As, Cd, Cu, Cr, Mg, Mn, Ni, Pb and Zn concentrations between sediment and water from estuary and port - I. Bejarano-Ramirez; Jose M. Jurado; R. Muñiz-Valencia; Á. Alcázar; Silvia G. Ceballos-Magaña; A. Olivos-Ortiz; O. Rangel (International Journal of Environmental Science and Technology, 2017)

Genesis and evolution of the Cerro Prieto Volcanic Complex, Baja California, Mexico - L. García-Sánchez; J. L. Macías; G. Sosa-Ceballos; J. L. Arce; V. H. Garduño-Monroy; R. Saucedo; D. R. Avellán; E. Rangel; P. W. Layer; H. López-Loera; V. S. Rocha; G. Cisneros; et al. (Bulletin of Volcanology, 2017)

Cyanobacteria in a eutrophicated reservoir in a semi-arid region in Brazil: dominance and microcystin events of blooms - Ruceline P. M. Lins; Luciana G. Barbosa; Alessandro Minillo; Beatriz S. O. De Ceballos (Brazilian Journal of Botany, 2016)

Effects of habitat deterioration on the population genetics and conservation of the jaguar - S. Roques; R. Sollman; A. Jácomo; N. Tôrres; L. Silveira; C. Chávez; C. Keller; D. Mello do Prado; P. Carignano Torres; C. Jorge dos Santos; X. Bernardes Garcia da Luz; W. E. Magnusson; et al. (Conservation Genetics, 2016)

El Ventorrillo, a paleostructure of Popocatépetl volcano: insights from geochronology and geochemistry - G. Sosa-Ceballos; J. L. Macías; F. García-Tenorio; P. Layer; P. Schaaf; G. Solís-Pichardo; J. L. Arce (Bulletin of Volcanology, 2015)

Conventional breeding, marker-assisted selection, genomic selection and inbreeding in clonally propagated crops: a case study for cassava - Hernán Ceballos; Robert S. Kawuki; Vernon E. Gracen; G. Craig Yencho; Clair H. Hershey (Theoretical and Applied Genetics, 2015)

Intermittent mixing processes occurring before Plinian eruptions of Popocatepetl volcano, Mexico: insights from textural–compositional variations in plagioclase and Sr–Nd–Pb isotopes - G. Sosa-Ceballos; J. E. Gardner; J. C. Lassiter (Contributions to Mineralogy and Petrology, 2014)

Transport of a Solvent Mixture Across Two Glove Materials When Applied in a Paint Matrix - Jackelin Q. Tran; Diana M. Ceballos; Russell L. Dills; Michael G. Yost; Michael S. Morgan (Archives of Environmental Contamination and Toxicology, 2012)

Therapeutic drug monitoring of posaconazole in hematology adults under posaconazole prophylaxis: influence of food intake - C. Eiden; J. C. Meniane; H. Peyrière; S. Eymard-Duvernay; G. Falher; P. Ceballos; N. Fegueux; M. Cociglio; J. Reynes; D. Hillaire-Buys (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Buoyancy of sub-Antarctic notothenioids including the sister lineage of all other notothenioids (Bovichtidae) - Daniel A. Fernández; Santiago G. Ceballos; Gabriela Malanga; Claudia C. Boy; Fabián A. Vanella (Polar Biology, 2012)

Isolation and characterization of ten microsatellite loci from the Patagonian notothenioid fish Eleginops maclovinus - S. G. Ceballos; M. F. Victorio; M. L. Lyra; D. A. Fernández (Conservation Genetics Resources, 2011)

Adjustment for missing plants in cassava evaluation trials - J. C. Pérez; H. Ceballos; I. C. Ramírez; J. I. Lenis; F. Calle; N. Morante; G. Jaramillo; M. Lentini (Euphytica, 2010)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Energy density of sub-Antarctic fishes from the Beagle Channel - D. A. Fernández; M. E. Lattuca; C. C. Boy; A. F. Pérez; S. G. Ceballos; F. A. Vanella; E. R. Morriconi; G. F. Malanga; D. R. Aureliano; S. Rimbau; J. Calvo (Fish Physiology and Biochemistry, 2009)

Mycorrhizal colonization and nitrogen uptake by maize: combined effect of tropical earthworms and velvetbean mulch - Angel I. Ortiz-Ceballos; Juan J. Peña-Cabriales; Carlos Fragoso; George G. Brown (Biology and Fertility of Soils, 2007)

Relationship between steroidogenesis and spermiation in Rana catesbeiana and Leptodactylus ocellatus - Cinthia Rosemblit; Andrea G. Pozzi; Nora R. Ceballos (Journal of Comparative Physiology B, 2006)

Viral reactivation and pseudotype production in an in vitro superinfection system with two different strains of HIV-1 - P. N. Fernández Larrosa; A. Ceballos; G. Andreani; S. Marquina; L. Martínez Peralta; R. D. Rabinovich (Archives of Virology, 2006)

Within-family genetic variation and epistasis in cassava (Manihot esculenta Crantz) adapted to the acid-soils environment - J. C. Perez; H. Ceballos; F. Calle; N. Morante; W. Gaitán; G. Llano; E. Alvarez (Euphytica, 2005)

Diallel inheritance of relevant traits in cassava (Manihot esculenta Crantz) adapted to acid-soil savannas - F. Calle; J. C. Perez; W. Gaitán; N. Morante; H. Ceballos; G. Llano; E. Alvarez (Euphytica, 2005)

Variation of quality traits in cassava roots evaluated in landraces and improved clones - A. L. Chávez; T. Sánchez; G. Jaramillo; J. M. Bedoya; J. Echeverry; E. A. Bolaños; H. Ceballos; C. A. Iglesias (Euphytica, 2005)

Genetic differentiation in silicicolous Echinospartum (Leguminosae) indicated by allozyme variability - A. Aparicio; R. G. Albaladejo; G. L. Ceballos (Plant Systematics and Evolution, 2002)

The Role of Prairie Dogs as a Keystone Species: Response to Stapp - B. Miller; R. Reading; J. Hoogland; T. Clark; G. Ceballos; R. List; S. Forrest; L. Hanebury; P. Manzano; J. Pacheco; D. Uresk (Conservation Biology, 2000)

Pregnenolone and progesterone metabolism by the testes of Bufo arenarum - L. F. Canosa; A. G. Pozzi; N. R. Ceballos (Journal of Comparative Physiology B, 1998)